S127 NIV in exacerbations of COPD: prognostication is not all baseless. (December 2018) - Hartley, TM; Lane, ND; Steer, J; Bourke, SC
Abstract : Background: Patients ventilated for ECOPD include those with and without chronic hypercapnia. Time to pH correction after instigation of ventilation has been associated with likely treatment success. However, prognostication prior to instigation of ventilation is poor indicating clinicians' notion of true adverse factors may be flawed. Methods: The derivation cohort of the NIV O utcome study comprises consecutive, unique patients hospitalised with a primary diagnosis of ECOPD receiving assisted ventilation. Key demographic and prognostic indices were collected from case-note review. Arterial blood gases were examined, a pH was only recorded as corrected when pH ≥7.35 was seen on an ABG post NIV initiation. Results: Data was collected on 489 patients admitted Dec-2008 to May-2013, 20 patients who survived to discharge but did not have a blood gas showing pH correction were assumed to belong to the >36 hour group. 5.5% received IMV. Outcomes categorised by base excess (BE) are shown in the table 1. Discussion: Those with likely concurrent metabolic acidaemia as measured by a negative BE have lower pH and much worse outcome. More interestingly from this cohort the higher the base excess at outset the lower the mortality. Amongst those with a BE >10 crudely indicating substantial chronic hypercapnia without complicating mixed acidaemia a large majority correct pH within 36 hours and mortality is low. Chronic hypercapnia is not an adverse prognostic feature. At time of presentation comparison results from 10 UK centres n=734 NIVO validation study will be available.